Analysis of Factor Affecting Nutrition Status on Children - Laili Rahayuwati; Ikeu Nurhidayah; Nur Oktavia Hidayati; Sri Hendrawati; Habsyah Saparidah Agustina; Rindang Ekawati (Jurnal Keperawatan Padjadjaran, 2019)
The problem of malnutrition remains overlooked in Indonesia, especially on children, caused by various factors. Indonesia is the 17th country with 3 nutrition problems, including stunting (short body), wasting (skinny body), and overweight (obesity). This research aims to analyze factors affecting nutrition status on children in the area of West Java Province, including the mother’s and the child’s socio-demographics factor, and the child’s health status. The research method was descriptive quantitative with cross-sectional approach. The number of samples is 810. The research was conducted in 6 districts that support Family Planning (KB), including Bandung District, Bandung City, West Bandung District, Subang District, Sumedang District, and Garut District. The quantitative analysis consisted of univariates using percentage and frequency distribution, as well as bivariate analysis using chi square test. The result of the research shows that nearly all toddlers have good nutrition status as much as 87.9%, and toddlers with malnutrition as much as 10.6%. The analysis factor shows that there is a relationship between the mother’s age (p = 0.048; OR = 1.583), family income (p = 0.010; OR = 1.803), delivery complications (p = 0.008; OR = 2.091), provision of exclusive breastfed milk (ASI) at the age of 0 - 6 years old (p = 0.000; OR = 2.321), provision of exclusive breast milk and complementary feeding given to babies before 6 months old (MPASI) at the age of 6 months to 2 years old (p = 0.002; OR = 2.037), and the child’s history of hospitalization (p = 0.008; OR = 2.055), while other factors are considered irrelevant. This research suggests that healthcare staff collaborate in providing knowledge to mothers on the provision of exclusive breast milk and complementary feeding as well as the prevention of illness on their children.